The Shape of the Dose-Response Relationship between Sugars and Caries in Adults. (February 2016) - Bernabé, E.; Vehkalahti, M.M.; Sheiham, A.; Lundqvist, A.; Suominen, A.L.
Dental caries is considered a diet-mediated disease, as sugars are essential in the caries process. However, some gaps in knowledge about the sugars-caries relationship still need addressing. This longitudinal study aimed to explore 1) the shape of the dose-response association between sugars intake and caries in adults, 2) the relative contribution of frequency and amount of sugars intake to caries levels, and 3) whether the association between sugars intake and caries varies by exposure to fluoride toothpaste. We used data from 1, 702 dentate adults who participated in at least 2 of 3 surveys in Finland (Health 2000, 2004/05 Follow-up Study of Adults' Oral Health, and Health 2011). Frequency and amount of sugars intake were measured with a validated food frequency questionnaire. The DMFT index was the repeated outcome measure. Data were analyzed with fractional polynomials and linear mixed effects models. None of the 43 fractional polynomials tested provided a better fit to the data than the simpler linear model. In a mutually adjusted linear mixed effects model, the amount of, but not the frequency of, sugars intake was significantly associated with DMFT throughout the follow-up period. Furthermore, the longitudinal association between amount of sugars intake and DMFT was weaker in adults who used fluoride toothpaste daily than in those using it less often than daily. The findings of this longitudinal study among Finnish adults suggest a linear dose-response relationship between sugars and caries, with amount of intake being more important than frequency of ingestion. Also, daily use of fluoride toothpaste reduced but did not eliminate the association between amount of sugars intake and dental caries.